Analysis of the implementation of character education in students as prospective teacher - Bantas, Maria Goretty; Ota, Maria Kristina; Taga, Gregorius; Tupen, Stefanus Notan (Univeritas Papua, 2024)
The aim of this research is to determine the implementation of character education in students as future teachers. Character education can form a complete human being with character, namely forming lifelong learners, and will actually be able to develop all students' potential in a balanced way (spiritual, emotional, intellectual, social and physical) which is adapted to the educational goals contained in the philosophy of the Indonesian nation, namely Pancasila. In a college environment, character education is nothing new. However, its implementation still requires more understanding which can be provided in general courses at universities. This research uses data collection methods, namely interview methods, observation and documentation methods. Validity test using source triangulation and 5-stage qualitative analysis from Miles and Huberman. From the research results, it was found that the implementation of character education in Flores University mathematics education study program students as teacher candidates through curriculum review courses can be seen from the embedded character values, namely discipline, hard work, creativity, independent responsibility and communicativeness.